Social Justice Based on the Pancasila Worldview: A Philosophical Analysis of Taxation and Structural Poverty in Indonesia - Adib Fattah Suntoro; Fajar Nur Rohim (Journal of Islamic and Occidental Studies, 2026)
This article philosophically analyzes the paradigm of social justice grounded in the Pancasila worldview as a response to taxation inequality and structural poverty in Indonesia. The study is based on the observation that the taxation system remains predominantly oriented toward technocratic and economistic considerations, while structural poverty continues to persist as a long-standing social problem. Unlike previous studies that have primarily emphasized the historical and ideological dimensions of Pancasila, this research positions Pancasila as a living worldview that provides ethical orientation for public policymaking. Employing a qualitative normative-philosophical approach based on library research and content analysis, the study integrates classical and modern theories of justice with the ideas of Indonesia’s founding figures to reconstruct the relationship between Pancasila values and taxation policy. The findings reveal that the fifth principle of Pancasila embodies the principles of redistribution, social solidarity, and moral responsibility, positioning taxation as an ethical instrument for achieving the common good through proportionate contributions from those with greater economic capacity to protect and empower vulnerable groups. State legitimacy derives not only from legal authority but also from its consistency in managing and redistributing tax benefits for public welfare. Therefore, Pancasila should be reaffirmed as an axiological principle that serves as the foundation for fiscal policy reform aimed at reducing inequality and addressing structural poverty in a sustainable manner.